2023
DOI: 10.1021/acschembio.3c00091
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Studies of the Novel Hexameric Endoribonuclease YicC

Abstract: The decay of mRNA is an essential process to bacteria. The newly identified E. coli protein YicC is a founding member of the UPF0701 family, and biochemical studies indicated that it is an RNase involved in mRNA degradation. However, its biochemical properties and catalytic mechanism are poorly understood. Here, we report the crystal structure of YicC, which shows an extended shape consisting of modular domains. While the backbone trace of the monomer forms a unique, nearly closed loop, the three monomers pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As we did here, Huang et al 9 also identified several arginine residues that contribute to RNA binding, including R30 and R280. Using a set of related RNA sequences as substrates, these authors reported that YicC recognizes primarily a GUG sequence.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As we did here, Huang et al 9 also identified several arginine residues that contribute to RNA binding, including R30 and R280. Using a set of related RNA sequences as substrates, these authors reported that YicC recognizes primarily a GUG sequence.…”
Section: Discussionsupporting
confidence: 78%
“…While we were preparing this manuscript, Huang et al . published their findings on the structural and biochemical characterization of E. coli YicC 9 . These authors determined a low resolution YicC crystal structure (4.05 Å), and confirmed that the protein forms a hexamer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation